Meta modernism: The emergence of a new era and the preservation of cultural artifacts through virtual reality and non-fungible tokens - Islam, Md Mahmud (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2022.